PERSEPSI KARYAWAN LPD SE-KECAMATAN DENPASAR UTARA TERHADAP EFEKTIVITAS PENERAPAN SIA, KECANGGIHAN TEKNOLOGI INFORMASI - Dirga Surya; Sukarta, Made Andy Pradana (KRISNA: Kumpulan Riset Akuntansi, 2025)
This study aims to analyze the perceptions of employees at Village Credit Institutions (LPD) in the North Denpasar District regarding the effectiveness of Accounting Information System (AIS) implementation and the sophistication of the technology utilized. The study is motivated by the crucial role of AIS and modern technology in enhancing efficiency, accuracy, and transparency in financial information management. Data were collected through questionnaires distributed to 54 respondents and analyzed using descriptive statistical methods. The findings show that perceptions of AIS effectiveness achieved an average score of 4.38, while perceptions of technological sophistication reached 4.36. Both results fall into the Very Good category, indicating that the information systems implemented have met user expectations in supporting operational activities and decision-making. These findings emphasize the importance of integrated technology and competent human resources in the successful implementation of AIS in LPDs.